Reimagining Marxism: The Role of Self-Managed Firms in Shaping a Decentralized Socialist Economy - Bruno Jossa (New Advances in Business, Management and Economics Vol. 3, 2025)
Economic research has provided convincing evidence that at least two production systems are possible at a post-capitalistic stage: a centrally planned system of public firms or a system of self-managed firms. The starting point for this paper is the finding that references to a system of self-managed firms as the future social order are quite exceptional in the published literature on Marxist thought. Despite ever more marked deviations of leftist political platforms from the centralised model of the URSS, it is clear that self-management has not taken the place of central planning in Marxist plans for the future. In contrast, the author came up with evidence that an analysis of the self-managed firm system may offer clues for a critical discussion of major points of Marxian theory, including the labour theory of value, alienation, dialectics or the subject-object inversion in capitalism. Accordingly, in the individual sections of this paper, each of these central aspects of Marxian theory will be separately addressed in the light of insights flowing from the economic theory of producer cooperatives. In conclusion, it is important to remark that the rejection of Marx’s value theory and Hegelian dialectics does not undermine the vitality of Marxism.